2012
DOI: 10.2174/1874196701205010006
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Bioinformatics and Computational Biology Approach Identifies New BH3-Only Protein Candidates

Abstract: In this study, we utilized an integrated bioinformatics and computational biology approach in search of new BH3-only proteins belonging to the BCL2 family of apoptotic regulators. The BH3 (BCL2 homology 3) domain mediates specific binding interactions among various BCL2 family members. It is composed of an amphipathic α-helical region of approximately 13 residues that has only a few amino acids that are highly conserved across all members. Using a generalized motif, we performed a genome-wide search for novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 102 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…A similar interaction has previously been reported in breast cancer cells treated with DNA-damaging reagents [25]. Recent analysis of the AVEN protein sequence has identified a BCL2 homology 3 (BH3) domain, indicating that AVEN is a novel member of the BCL2 family of apoptotic regulators [52]. Evidence has shown that when a BH3 domain peptide adopts an α-helical conformation, its affinity for binding anti-apoptotic BCL2 proteins, such as BCL-x L , increases [53,54].…”
Section: P4 Signalling and Apoptosissupporting
confidence: 73%
“…A similar interaction has previously been reported in breast cancer cells treated with DNA-damaging reagents [25]. Recent analysis of the AVEN protein sequence has identified a BCL2 homology 3 (BH3) domain, indicating that AVEN is a novel member of the BCL2 family of apoptotic regulators [52]. Evidence has shown that when a BH3 domain peptide adopts an α-helical conformation, its affinity for binding anti-apoptotic BCL2 proteins, such as BCL-x L , increases [53,54].…”
Section: P4 Signalling and Apoptosissupporting
confidence: 73%
“…In addition to the previously mentioned hydrophobic residues on one face of the Bak-BH3 α-helix, Arg76 and Asp83 located on the other face of the helix are also important for binding [11]. Thus, towards the development of potent, pan-Bcl-2 antagonists, we wished to design amphipathic α-helix mimetics that would achieve more superior α-helix mimicry than ever reported before, as well as, potentially, better selectivity profiles against non-Bcl-2 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative strategy to the disruption of this protein–protein interaction centers on the observation that the BH3 domains of the pro-apoptotic proteins become α-helical upon binding their anti-apoptotic partners [11]. Accordingly, small-molecules have been designed to reproduce the relative projections of key hydrophobic side chains found on one face of the BH3 α-helix.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AVEN is able to bind to the DNA damage response regulating kinase ATM (ataxia telangiectasia mutated) and is phosphorylated by ATM at S135 and S308 (Guo et al, 2008). In addition, a potential nuclear export sequence (NES) to exists between aa 282-293 (Esmaili et al, 2010) and a putative BH3 motif (for binding to Bcl-xL) has been predicted to be located between aa 141-153 (Hawley et al, 2012).…”
Section: Descriptionmentioning
confidence: 99%